2006
DOI: 10.1128/aem.01924-05
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation ofMycobacterium aviumsubsp.paratuberculosisin Cow's Milk by Means of High Hydrostatic Pressure at Mild Temperatures

Abstract: Two strains of Mycobacterium avium subsp. paratuberculosis (3644/02 and ATCC 19698) were inoculated (approximately 6 log CFU/ml) into sterilized milk to evaluate inactivation by high hydrostatic pressure. Reductions of M. avium subsp. paratuberculosis increased with pressure level. Significant differences were also found between M. avium subsp. paratuberculosis strains and between the media used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
1
11
2
Order By: Relevance
“…600 MPa without heat treatment resulted in only two samples with surviving Map above the limit of detection (1 CFU ml −1 ) they were not included in the statistical analysis. The observation in the work reported here that 500 MPa resulted in a significantly greater reduction in viable numbers than 400 MPa compared with the control (Table 1) is not in agreement with Lopez‐Pedemonte et al. (2006) who found a significant difference ( P < 0·05) in viable Map after 500 MPa but not 400 MPa compared with their control (0·1 MPa).…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…600 MPa without heat treatment resulted in only two samples with surviving Map above the limit of detection (1 CFU ml −1 ) they were not included in the statistical analysis. The observation in the work reported here that 500 MPa resulted in a significantly greater reduction in viable numbers than 400 MPa compared with the control (Table 1) is not in agreement with Lopez‐Pedemonte et al. (2006) who found a significant difference ( P < 0·05) in viable Map after 500 MPa but not 400 MPa compared with their control (0·1 MPa).…”
Section: Discussioncontrasting
confidence: 94%
“…The significant improvement in Map recovery on 7H10 medium compared with HEYM following high-pressure treatment in this study is in agreement with Lopez- Pedemonte et al (2006) who also found better recovery of two Map strains on agar-solidified 7H9 medium compared with HEYM after high-pressure processing.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Other attempts to inactivate M. avium subsp. paratuberculosis include the uses of UV irradiation (2), pulsed electric fields (38), and hydrostatic pressure (30). Another possible route of transmission of M. avium subsp.…”
mentioning
confidence: 99%